Review of a book by Srećko Stopić: Synthesis of metallic nanosized particles by ultrasonic spray pyrolysis - Stopić, Milena D. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Nanotechnology belongs to the key innovative technologies for powder production. Ultrasonic spray pyrolysis is a versatile method for the formation of nanosized particles of metals, oxides and composites. This work deals with  Ag, Cu and Au nanoparticles formed by ultrasonic spray pyrolysis using the horizontal and vertical reactor. Furthermore, a direct synthesis of Ru-TiO2 and RuO2-TiO2 nanoparticles with the core and shell structure was investigated. The molar fractions of precursors, solvent type, and the process temperature play the crucial role in the formation of core and shell structures. Moreover, the influence of the reaction parameters (temperature, residence time,  solution concentration and ultrasonic frequency) on the morphological characteristics of the prepared nanoparticles was studied. A decrease in the solution concentration decreases the final nanoparticle size. An increase in temperature from 150°C to 1000°C leads from an irregular form to a more spherical one. Subsequently, a model of metallic nanoparticle formation from an aerosol droplet could be proposed. Using ultrasonic spray pyrolysis, ideal spherical metallic particles were obtained at temperatures above the melting point. A scanning mobility particle sizer (SMPS) was used for the on-line determination of nanoparticle size distribution. The collection of nanosized particles was performed in an electrostatic field. The scale up of the ultrasonic spray pyrolysis method was successfully applied for the synthesis of silver powder from a water solution of silver nitrate.
Keywords: metal; powders; synthesis; ultrasonic spray pyrolysis